Diagnosis of fungal diseases in quinoa (Chenopodium quinoa Willd) in Burkina Faso - Louis NEBIE; Abdalla DAO; Tobdem Gaston DABIRE; Schémaéza BONZI; Jacob SANOU; Irénée SOMDA (Scientific Reports)
Abstract Quinoa is an Andean pseudo-cereal crop that is mainly cultivated for its energy and protein-rich, gluten-free seeds. Quinoa is currently being popularized in Burkina Faso, but manifestations of fungal diseases have been observed on the plants. The aim of this study was to establish a causal relationship between the observed symptoms and the associated fungal pathogens. Samples of symptomatic organs were collected from the three agro-ecological zones and examined for fungal pathogen species via isolation on media. A total of six (6) diseases and twenty-nine (29) fungal species were described and identified in the collected organs. The diseases were present in the following proportions: (i) panicle browning followed by complete plant drying (45.36%), (ii) brown crown rot (41.20%), (iii) brown stalk rot (27.31%), (iv) damping-off (22.68%), (v) chlorosis with necrotic brown leaf spots (19.33%), and (vi) plant wilting (13.88%). The essential epidemiological factors of these pathologies are discussed.